1995
DOI: 10.1128/jvi.69.9.5838-5842.1995
|View full text |Cite
|
Sign up to set email alerts
|

High levels of anti-human immunodeficiency virus type 1 (HIV-1) memory cytotoxic T-lymphocyte activity and low viral load are associated with lack of disease in HIV-1-infected long-term nonprogressors

Abstract: Lack of disease in long-term nonprogressors with human immunodeficiency virus type 1 (HIV-1) infection was strongly associated with very low copy numbers of HIV-1 DNA and RNA in peripheral blood mononuclear cells and plasma and the presence of high levels of anti-HIV-1 CD8 ؉ memory cytotoxic T lymphocytes specific for Gag, Pol, and Env, compared with levels present in intermediate and advanced progressors. CD8 ؉ memory cytotoxic T lymphocytes may have an important role in controlling HIV-1 replication and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(114 citation statements)
references
References 37 publications
5
108
0
1
Order By: Relevance
“…CD4 was categorized as shown in Table 3 based on the 1993 revised classification system by the Centres for Disease Control and Prevention (CDC) (1992). The viral load categorization was based on published research that showed that people with viral loads below 10,000 copies ml −1 of blood did not show disease progression in greater than a 9-year period compared to people with higher viral loads (Rinaldo et al 1995) and on the World Health Organization's designation of viral loads of >10,000 copies ml −1 as evidence of virological failure (WHO 2000). Variables that were statistically significant at p<0.1 on bivariate analysis and those known to be associated with aflatoxin based on the extant literature were incorporated into models using the backward step-wise technique (Hosmer and Lemshow 2000).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 was categorized as shown in Table 3 based on the 1993 revised classification system by the Centres for Disease Control and Prevention (CDC) (1992). The viral load categorization was based on published research that showed that people with viral loads below 10,000 copies ml −1 of blood did not show disease progression in greater than a 9-year period compared to people with higher viral loads (Rinaldo et al 1995) and on the World Health Organization's designation of viral loads of >10,000 copies ml −1 as evidence of virological failure (WHO 2000). Variables that were statistically significant at p<0.1 on bivariate analysis and those known to be associated with aflatoxin based on the extant literature were incorporated into models using the backward step-wise technique (Hosmer and Lemshow 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although this initial study defined that cytotoxic activity was present within HIV-infected subjects, many subsequent studies have found that HIV-specific killing function is deficient in chronically infected individuals (73)(74)(75) as well as acute infection (4,76). These studies, however, have come full circle in more recent works, with a more detailed understanding of cytotoxic potential in chronic HIV infection (32,33,(77)(78)(79)(80).…”
Section: Killing In the Name Of Protectionmentioning
confidence: 99%
“…HIV-1 replication is characterized by a relatively high mutation rate, as well as an enormous amount of viral replication, especially during the acute phase of the infection. CTL are thought to play a major role in down-regulating the very large number of infected cells that exist at peak virus load during acute infection (Borrow et al 1994;Koup et al 1994;Langlade-Demoyen et al 1994;Rinaldo et al 1995;Rowland-Jones et al 1995;Harrer et al 1996;Yang et al 1997;Van Baalen et al 1998;Schmechel et al 2001). Given the high mutation rate and the large amount of viral replication, it is possible that by the time virus load has reached its peak, escape mutants have been generated and preexist even before the CTL response kicks in.…”
Section: Discussionmentioning
confidence: 99%